2018
DOI: 10.9734/ajob/2018/45024
|View full text |Cite
|
Sign up to set email alerts
|

Helminth Parasites of Gobies from Two Creeklets of the New Calabar River, Rivers State, Nigeria

Abstract: Aim: An animal species either serves as a definitive, a paratenic or an intermediate host to helminth parasites which may be species or site specific. This study was undertaken to investigate the intestinal helminth parasites of gobies (Bostrychus africanus and Periophthalmus papilio) collected from two creeklets of the New Calabar River. Study Design: Fifteen samples of each species were collected (from two stations fortnightly) measured and weighed. All fish was dissected and intestinal parasites were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…The concentration of lead (Pb) in the water samples obtained from S1OK was 0.034mg/L while that of the S3KR which was a surface water had 0.038 mg/L. Ugbomeh et al (2012) reported the variation in the levels of heavy metals in aquatic sources may vary from one geophysical location to seasonal; they observed a sharp fluctuation in titre of heavy metals during the dry season along the Soku Oil field Area of Niger Delta In another study, Akporido and Onianwa (2015) reported 39 µg/L in the surface water of Esi River in Western Niger Delta, the concentration was higher than the recommended limits while Obire et al (2003) reported higher levels of lead in the Benin River at Koko with a concentration value of 2270 µg/L. These findings also suggest that the impact of oil exploration could impact on the quality and quantity of concentration of oxygen in most water resources.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of lead (Pb) in the water samples obtained from S1OK was 0.034mg/L while that of the S3KR which was a surface water had 0.038 mg/L. Ugbomeh et al (2012) reported the variation in the levels of heavy metals in aquatic sources may vary from one geophysical location to seasonal; they observed a sharp fluctuation in titre of heavy metals during the dry season along the Soku Oil field Area of Niger Delta In another study, Akporido and Onianwa (2015) reported 39 µg/L in the surface water of Esi River in Western Niger Delta, the concentration was higher than the recommended limits while Obire et al (2003) reported higher levels of lead in the Benin River at Koko with a concentration value of 2270 µg/L. These findings also suggest that the impact of oil exploration could impact on the quality and quantity of concentration of oxygen in most water resources.…”
Section: Discussionmentioning
confidence: 99%
“…However, scientific reporting of parasitic infections in these fish species is scanty. Ugbomeh et al [4] found Ascaridida nematodes in B. africanus and P. papilio, with higher parasite infection prevalence in B. africanus. Robert et al [13] found Raphidascaroides africanus in Rumuolumeni and Afikpo markets in Port Harcourt, Nigeria; while, Elele and Aziaka [14] reported the presence of monogenean, digenean, cestode and nematode parasites in Periophthalmus species obtained from some waterfronts in Rivers State, Nigeria.…”
Section: Gobiidsmentioning
confidence: 98%
“…Gobiids, such as Bostrychus africanus and Periophthalmus papilio, are carnivores that feed on crustaceans and other benthic invertebrates, small fishes and insects. Many species pass through a marine larval stage during which they feed on plankton [4]. The analysis of fish stomach content, which depends on food availability and varies by location, provides information about their feeding habits and culture potential [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous mermithid nematodes, rotifers, rickettsia and other bacteria, and viruses are known from woodlice and land crabs ( Provenzano 1983 ; Federici 1984 ; Rigaud and Moreau 2004 ; Wang 2011 ; Ugbomeh and Bajor 2015 ). In particular, common iridoviruses ( Iridoviridae ) confer an iridescent blue color to the body of the infected woodlice ( Williams 2008 ).…”
Section: Diversity and Abundance In Terrestrial Habitatsmentioning
confidence: 99%